Kritik Hadits Nikah Mut’ah Perspektif Sunnah (Studi Analisis Sanad dan Matan Hadits tentang Larangan Nikah Mut’ah) - Y, Yulianto (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2020)
Based on studies that the authors have done, this hadith is one of the proofs used by Ahlus Sunnah wal Jama'ah in forbidding mut'ah marriage. Because based on historical facts and nasikh mansukh studies, the hadith has abrogated the validity of the hadith which allows mut'ah mut'ah.Other Ahlus Sunnah, another with the Shi'a group who until now still hold fast to the validity and even do mut'ah marriage among them. They - the Shi'a group - loudly reject the hadiths which explain the forbidden mut'ah marriage, among them is the hadith about establishing the prohibition of mut'ah marriage until doomsday, that is the hadith which is the object of this research. From this point of difference, the researcher feels it is necessary to conduct further research on the hadith mut'ah marriage ban forever. The research will be conducted from two paths, namely: (1) sanad pathway and (2) matan pathway. The path of sanad, will be carried out by examining the relationship between one rawi rawi and the rawi, the level of dlobit and their justice, as well as the assessment of the scholars about their credibility so as to produce ittshol sanad (continuation of the sanad), 'is (justice), and the dynamics of the rawi ( intelligence and memory of peawi) perfectly or not. While the pathway matan, will be done by searching for the answer 'and sawahid from other paths so that it can be used as a comparison and reinforcement of the hadith under study. From in-depth studies and research on the quality and quantity of the hadith about the prohibition of mut'ah marriage forever, then in terms of quantity, the hadith is dignified hasan lidzatihi; while in terms of quantity dignified on Sunday because it is only narrated by a friend, namely Sabroh bin Ma'bad al-Juhanni. But the dignity of hasan lidzatihi later rose to saheeh lighoirihi because he had a shaheed and an answer 'from another hadith.